Effect of Magnesium, Bradyrhizobium Inoculation, Initial Moisture Content and Storage Container on the Vigour Index of Groundnut Seed (Bangladesh Journal of Scientific and Industrial Research, 2008)
The study was performed to determine the effect of magnesium and Bradyrhizobium fertilized seed at different initial moisture content of seed and storage container on the vigour index of groundnut seed. Results revealed that increase in the vigour index was observed with the doses of magnesium up to 10 kg/ha in storage but the seeds obtained from inoculation failed to check the deterioration. Results of vigour index indicated that groundnut seeds obtained from magnesium andBradyrhizobium fertilizer elements during production and stored in polythene bags can retain better seed quality, provided seeds were dried to a safe moisture level of 7.25%. Key words: Groundnut seed, Magnesium, Inoculation, Moisture content, vigour index. DOI: 10.3329.bjsir.v43i1.855Bangladesh J. Sci. Ind. Res. 43(1), 37-46, 2008